Analysis and design of accounting information system national health insurance acceptance cycle at Fatmawati Central General Hospital - Ahmad Qamardin (Trigin Publisher, 2023)
This research aims to analyze and design a client-server-based accounting information system at Fatmawati Central General Hospital. In this current condition, the reporting system is manual or still relies on Excel form, resulting in significant time consumption and inefficiency in presentation. The accounting cycle relevant to this research is the revenue cycle. This study utilized a Research and Development study through the Object-Oriented Analysis Design (OOAD) method, which focuses on model development using the Unified Modeling Language (UML). Data collection was conducted through interviews, observations, and documentation in order to obtain the necessary data. It is expected that this research could produce a design of a client-server-based accounting information system for the National Health Insurance claims acceptance cycle that aligns with the hospital's business processes